Thermal acclimation influences the growth and toxin production of freshwater cyanobacteria. Issue 1 (29th May 2021) - Layden, Tamara J.; Kremer, Colin T.; Brubaker, Delaney L.; Kolk, Maeve A.; Trout‐Haney, Jessica V.; Vasseur, David A.; Fey, Samuel B.
Abstract: Understanding how altered temperature regimes affect harmful cyanobacterial bloom formation is essential for managing aquatic ecosystems amidst ongoing climate warming. This is difficult because algal performance can depend on both current and past environments, as plastic physiological changes (acclimation) may lag behind environmental change. Here, we investigate how temperature variation on sub‐weekly timescales affects population growth and toxin production given acclimation. We studied four ecologically important freshwater cyanobacterial strains under low‐ and high‐nutrient conditions, measuring population growth rate after acclimation and new exposure to a range of temperatures. Cold‐acclimated populations (15.7°C) outperformed fully acclimated populations (held in constant conditions) across 65% of thermal environments, while hot‐acclimated populations (35.7–42.6°C) underperformed across 75% of thermal environments. Over a 5‐day period, cold‐acclimated Microcystis aeruginosa produced ~2.5‐fold more microcystin than hot‐acclimated populations experiencing the same temperature perturbation. Our results suggest that thermal variation and physiology interact in underappreciated ways to influence cyanobacterial growth, toxin production, and likely bloom formation.